General practitioners’ perceptions on opportunistic single-time point screening for atrial fibrillation: A European quantitative survey - Vermunicht, Paulien; Grecu, Mihaela; Deharo, Jean-Claude; Buckley, Claire M.; Palà, Elena; Mairesse, Georges H.; Farkowski, Michal M.; Bergonti, Marco; Pürerfellner, Helmut; Hanson, Coral L.; Neubeck, Lis; Freedman, Ben; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background There is no clear guidance on how to implement opportunistic atrial fibrillation (AF) screening in daily clinical practice. Objectives This study evaluated the perception of general practitioners (GPs) about value and practicalities of implementing screening for AF, focusing on opportunistic single-time point screening with a single-lead electrocardiogram (ECG) device. Methods A descriptive cross-sectional study was conducted with a survey developed to assess overall perception concerning AF screening, feasibility of opportunistic single-lead ECG screening and implementation requirements and barriers. Results A total of 659 responses were collected (36.1% Eastern, 33.4% Western, 12.1% Southern, 10.0% Northern Europe, 8.3% United Kingdom & Ireland). The perceived need for standardized AF screening was rated as 82.7 on a scale from 0 to 100. The vast majority (88.0%) indicated no AF screening program is established in their region. Three out of four GPs (72.1%, lowest in Eastern and Southern Europe) were equipped with a 12-lead ECG, while a single-lead ECG was less common (10.8%, highest in United Kingdom & Ireland). Three in five GPs (59.3%) feel confident ruling out AF on a single-lead ECG strip. Assistance through more education (28.7%) and a tele-healthcare service offering advice on ambiguous tracings (25.2%) would be helpful. Preferred strategies to overcome barriers like insufficient (qualified) staff, included integrating AF screening with other healthcare programs (24.9%) and algorithms to identify patients most suitable for AF screening (24.3%). Conclusion GPs perceive a strong need for a standardized AF screening approach. Additional resources may be required to have it widely adopted into clinical practice.